Oral Administration of the Endocannabinoid Anandamide during Lactation: Effects on Hypothalamic Cannabinoid Type 1 Receptor and Food Intake in Adult Mice - Carolina Aguirre; Valeska Castillo; Miguel Llanos (Journal of Nutrition and Metabolism)
We have previously shown that administration of the endocannabinoid anandamide (AEA) during lactation leads to overweight, increased body fat accumulation, and insulin resistance in adult mice. This study was designed to elucidate if these effects are due to increased food intake, stimulated by an augmented abundance and binding ability of the hypothalamic cannabinoid type 1 receptor (CB1R). With this aim, male mice pups were treated with a daily oral dose of AEA during lactation. Adult mice were also treated with a single oral dose of AEA, to evaluate acute food intake during 4 h. At 21 and 160 days, CB1R protein abundance was calculated by western blot analysis. Capacity of hypothalamic membranes to specifically bind the radioligand 3[H]-CP55.940 was also measured. Western blots showed a 72% increase in CB1R abundance in AEA-treated 21-day-old mice, without differences in adult mice. Additionally, specific binding of 3[H]-CP55.940 to hypothalamic membranes from adult mice was significantly lower in those mice treated with AEA during lactation. Moreover, AEA did not stimulate acute food intake in both, AEA-treated and control mice. Results suggest that metabolic alterations found in adult mice because of AEA treatment during lactation are not associated with hypothalamic CB1R.